2019
DOI: 10.14808/sci.plena.2019.090201
|View full text |Cite
|
Sign up to set email alerts
|

Influência da qualidade de luz no crescimento e acúmulo de voláteis de Mentha spicata cultivada in vitro

Abstract: Os objetivos deste trabalho foram investigar a influência da qualidade da luz no crescimento e no acúmulo de constituintes voláteis de Mentha spicata cultivada in vitro. Segmentos nodais de plântulas já estabelecidas foram mantidos sob lâmpadas fluorescentes e diodos emissores de luz (LEDs) com as regiões espectrais nas cores verde, amarelo, vermelho, azul e branco, e nas combinações entre vermelho e azul (1:1; 2:2 e 2:1). Após 45 dias, parâmetros de crescimento, área foliar, índices de crescimento, pigmentos … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…When SLA was evaluated, it was found that, among all treatments, there was a significant difference only with the superiority of values for seedlings produced in MHS in relation to the conventional system, when produced in tubettes, with no differences between containers or cultivars used (Table 2). SLA represents the ratio between leaf area and leaf dry biomass; it is a factor of physiological importance, as it describes the destination of leaf biomass per unit area (Cunha et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…When SLA was evaluated, it was found that, among all treatments, there was a significant difference only with the superiority of values for seedlings produced in MHS in relation to the conventional system, when produced in tubettes, with no differences between containers or cultivars used (Table 2). SLA represents the ratio between leaf area and leaf dry biomass; it is a factor of physiological importance, as it describes the destination of leaf biomass per unit area (Cunha et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Young plants tend to have higher LMR values since, at the beginning of growth, a greater allocation of photoassimilates to the leaves is necessary in relation other tissues, which will grow from the material transported from the leaves (Cunha et al, 2019). In this context, it can be inferred that the seedlings produced in the nursery with tubettes had their development delayed for presenting lower values in relation to the other treatments, that is, the conventional system proved to be less efficient than MHS, which can also be verified by observing data related to height and number of leaves (Table 1).…”
Section: Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…As for light sources, the best results observed in the combinations of blue and red may be related to the ability of these wavelengths to better excite photoreceptors (phytochromes, phototropins, and cryptochromes), thus increasing photosynthetic activity (Dou et al 2017). Furthermore, the greater proportion of blue to red wavelengths (3:1) absorbed by phototropin and cryptochromes may be associated with leaf expansion since phototropin is related to this function (Macedo et al 2011;Cunha et al 2019). Taiz et al (2017) reported that the quality of light provided to plant material is considered important because it regulates plant morphogenesis and growth.…”
Section: In Vitro Growth -120 Daysmentioning
confidence: 99%
“…Taiz et al (2017) reported that the quality of light provided to plant material is considered important because it regulates plant morphogenesis and growth. However, white light is a mixture of low intensities of red and blue and other wavelengths of low-efficiency light (Cunha et al 2019). This may be related to the higher values observed in white light treatments and in combinations of blue and red.…”
Section: In Vitro Growth -120 Daysmentioning
confidence: 99%